Women, feminism and social change in argentina, chile and uruguay, 1980-1940 (1996)
Asunción Lavrin. Women, feminism and social change in Argentina, Chile and Uruguay, 1890-1940. Lincoln and London: University of Nebraska Press, 1995, 481 páginas. Tercer volúmen de la serie Engendering Latin America.